ANALISIS TINDAK TUTUR PRAGMATIK KEKERASAN PADA NOVEL YANG TELAH LAMA PERGI KARYA TERE LIYE - Haedariah Haedariah; Nuryadin Nuryadin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The problem in this study is how the Pragmatic Speech Acts of Violence in the Novel Yang Sudah Lama Pergi by Tere Liye, this study aims to describe the Pragmatic Speech Acts of Violence in the Novel. The method in this study is descriptive qualitative where the author will describe the data found in such a way as to obtain a complete picture of the research object. The type of research used to analyze this novel is library research. Data collection techniques used in this study are reading and note-taking techniques. The quotes found by the researcher are divided into four parts: Indirect Speech Acts of Violence, Direct Speech Acts of Violence, Repressive Speech Acts of Violence, and Alienative Speech Acts of Violence.